Signal Transduction Pathways for Mouse Platelet Membrane Adhesion Receptors - Law, Debbie A.; Nannizzi-Alaimo, Lisa; Cowan, Kyra J.; Prasad, K. S. Srinivasa; Ramakrishnan, Vanitha; Phillips, David R. (Thrombosis and Haemostasis, 1999)
The study of genetic bleeding disorders provided the first link between platelet functions and specific membrane glycoproteins. Two examples are well known and have been the subject of numerous reviews. First, Glanzmann’s thrombasthenia is a bleeding disorder caused by a defect of platelet aggregation in which the glycoprotein αIIbβ3 (GP IIb-IIIa) is either lacking or is expressed but is defective.1 We now know that αIIbβ3 exists on the surface of unstimulated platelets in an inactive form but, through a process known as “inside-out” signaling, responds to platelet stimulation to become a receptor for soluble fibrinogen and von Willebrand factor (vWF) to mediate platelet aggregation. αIIbβ3 is also known to bind immobilized fibrinogen and, through a process known as “outside-in” signaling, to induce platelet stimulation.2 A second example is Bernard-Soulier syndrome, a bleeding disorder caused by the failure of platelets to bind to subendothelial matrices due to the lack of or defective GP Ib-IX-V.3 It is now known that GP Ib-IX-V binds to vWF to mediate the adhesion of unstimulated platelets to injured blood vessel walls.4,5 GP Ib-IX-V interactions also induce platelet stimulation, a process mediated by signaling through GP Ib-IX-V.6 The mechanisms responsible for the binding of adhesive proteins to αIIbβ3 and GP Ib-IX-V are beginning to be understood and, as such, targets for therapeutic intervention have been identified. Three parenteral αIIbβ3 antagonists have demonstrated a therapeutic benefit in large-scale clinical trials of acute coronary syndromes, including unstable angina, non Q-wave myocardial infarction, and percutaneous intervention, and are now commercially available.7 Many orally available αIIbβ3 antagonists are presently in clinical trials. Although GP Ib antagonists have not been pursued as aggressively, animal studies have shown that they do have a proven antithrombotic benefit.8 Despite these advances in the understanding of glycoprotein ligand binding and development of therapeutic antagonists of adhesive protein receptors, the mechanisms responsible for transducing signals through these receptors have remained elusive.It is now established that signal transduction reactions through αIIbβ3 and GP Ib-IX-V are not only involved in platelet aggregation to cause vessel occlusions, but also that glycoprotein signaling affects thrombus growth and stability, as well as the biology and perhaps the pathology of the vessels in which aggregates occur. In one example, platelet-derived growth factor (PDGF), secreted in response to αIIbβ3 signaling from the α-granules of aggregated platelets, is a primary smooth muscle cell mitogen and is believed to be involved not only in the response to vascular injury but also in atherosclerotic lesion progression.9,10 In another example, CD 154 (previously termed CD40 ligand) redistributes from α-granule membranes to the surface of aggregated platelets in response to αIIbβ3 signaling.11 CD 154 is an important inflammatory mediator that induces the release of cytokines from endothelial and smooth muscle cells, initiates vascular inflammation, and participates in atherosclerotic lesion progression.12 A third example involves the assembly of prothrombinase and factor Xase on the surface of aggregated platelets, enabling platelet thrombi to be procoagulant and accounting for the apparent anticoagulant activity of αIIbβ3 antagonists.13,14 In addition, platelet aggregates also display fibrinogen and vWF bound to platelet membrane glycoproteins that function to recruit additional platelets and, therefore, enhance thrombus growth.15 More recent data also indicate that platelet aggregation induces de novo protein synthesis.16,17 These and other events are secondary to the initial adhesion and aggregation reactions of platelets and are consequences of signaling reactions induced by the adhesion and aggregation receptors. Thus, characterization of the membrane glycoprotein signal transduction pathways has become essential, not only to understand platelet function, but also to determine whether there are additional ways by which platelet-mediated pathologies can be regulated.Platelet membrane glycoprotein signaling reactions either do not occur in nucleated cells normally used for transfection studies or are insufficiently characterized. Accordingly, the use of genetics to study mechanisms of platelet adhesive protein receptor signaling has been limited. The advent of technologies that facilitate genetic manipulations in the mouse genome has produced new ways to define protein function and determine the structure-function relationships of individual proteins and is proving of value in unraveling signal transduction pathways in platelets. Although one should always be cautious in extrapolating data from mouse to human platelets (as demonstrated by the PAR receptors, see below), it is impressive that much of what has been learned about platelets appears to apply to both mouse and human. Indeed, this review summarizes the status of genetic manipulations of the mouse genome that have contributed to our understanding of platelet membrane adhesion receptor signaling in platelets.